Analysis of metakaolin as partial substitution of ordinary portland cement in reactive powder concrete - Abellán-García, Joaquín; Torres, Nancy; Santofimio V, Maria (ASTM International, 2020)
Over the last 20 years, remarkable advances have taken place in the research on reactive powder concrete (RPC). However, because of the high contents of cement and silica fume (SF) usually used in those types of concrete, the cost and environmental impact of RPC is considerably higher than conventional concrete. Hence, the use of supplementary cementitious materials as partial substitution of cement and SF has been an object of great interest by the scientific community. However, the replacement of cement and SF can result in the deterioration of certain properties of RPC, such as the early strength; however, RPC usually needs great amounts of cement and SF. This work presents a study to analyze the effect of metakaolin (MK) as a partial substitute of cement in a previously optimized mixture of RPC using statistical tools such central composite design, main effect plot analysis, and response surface methodology. In addition to MK, supplementary cementitious materials such as SF, limestone powder and recycled glass powder, and fine Type III cement were used. Based on the laboratory experiments results and statistical analysis, it was concluded than MK develops a high activity in the hydration process of RPC, helping it reach high strength at early ages, such as 1 and 7 days, which may be of interest for applications such as the connection of prefabricated elements or accelerated bridge construction. However, the effect of the partial substitution of Type III cement by MK on 28-day compressive strength was nonsignificant. Moreover, the MK inclusion in RPC provides a significant decrease in workability as the amount of MK increases.

En los últimos 20 años se han producido notables avances en la investigación sobre el hormigón reactivo en polvo (RPC). Sin embargo, debido a los elevados contenidos de cemento y humo de sílice (SF) que suelen emplearse en esos tipos de hormigón, el coste y el impacto medioambiental del RPC son considerablemente superiores a los del hormigón convencional. De ahí que el uso de materiales cementantes suplementarios como sustitución parcial del cemento y el SF haya sido objeto de gran interés por parte de la comunidad científica. Sin embargo, la sustitución del cemento y el SF puede provocar el deterioro de ciertas propiedades del RPC, como la resistencia temprana; además, el RPC suele necesitar grandes cantidades de cemento y SF. Este trabajo presenta un estudio para analizar el efecto del metacaolín (MK) como sustituto parcial del cemento en una mezcla previamente optimizada de RPC utilizando herramientas estadísticas como el diseño compuesto central, el análisis de parcelas de efectos principales y la metodología de superficie de respuesta. Además del MK, se utilizaron materiales cementantes suplementarios como SF, polvo de caliza y polvo de vidrio reciclado, y cemento fino de tipo III. Basándose en los resultados de los experimentos de laboratorio y el análisis estadístico, se concluyó que el MK desarrolla una alta actividad en el proceso de hidratación del RPC, ayudando a que alcance una alta resistencia a edades tempranas, como 1 y 7 días, lo que puede ser de interés para aplicaciones como la conexión de elementos prefabricados o la construcción acelerada de puentes. Sin embargo, el efecto de la sustitución parcial del cemento Tipo III por MK sobre la resistencia a compresión a 28 días no fue significativo. Además, la inclusión de MK en el EPR proporciona una disminución significativa de la trabajabilidad a medida que aumenta la cantidad de MK.
Keywords: Reactive powder concrete; Supplementary cementitious materials; Packing density; Metakaolin; Central composite design; Response surface methodology